The school-to-work transition, education-job mismatch and the effect on income / Mohd Amirul Rafiq Abu Rahim - Mohd Amirul Rafiq , Abu Rahim (2024)
This study investigates the interplay between school-to-work transition (SWT), education-job mismatch, and income among young workers in Malaysia. Using data from the 2018 Survey on School-to-Work Transition of Young Malaysians (SWTS), the research addresses gaps in the literature by analysing characteristics that clarify relationships unique to Malaysia. The study explores determinants and quality of SWT length, education-job mismatch, and their effects on income. The analysis highlights several demographic characteristics playing significant roles in influencing the quality of SWT length and education-job mismatch. The study reveals that tertiary-educated young workers in Malaysia secure jobs faster but face prolonged transition periods. Additionally, overeducated individuals experience significant income penalties, and gender composition influences income differentials, with broader gender income gaps among overeducated workers. The study emphasises the need for comprehensive labour market policies, advocating for a broader perspective beyond economic growth, with a focus on enhancing both passive and active labour market policies for vulnerable populations, particularly the younger generation.